2005
DOI: 10.1007/s00436-005-1374-y
|View full text |Cite
|
Sign up to set email alerts
|

Is Leishmania (Viannia) braziliensis preferentially restricted to the cutaneous lesions of naturally infected dogs?

Abstract: Nineteen dogs naturally infected with Leishmania (Viannia) braziliensis were studied in order to determine the presence of the parasite outside cutaneous lesions. Eleven (57.9%) animals showed single cutaneous or mucosal lesions and eight (42.1%) presented two or three lesions. Twenty-eight active lesions were biopsied. Isolation in culture and characterization by enzyme electrophoresis were possible in 100% of cases and amastigote forms were visualized upon histopathological examination in three samples (n=25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
(20 reference statements)
0
16
0
2
Order By: Relevance
“…In Paracatu, Minas Gerais, 5% out of 267 dogs with positive serology for VL were asymptomatic (Dias et al 2011). The presence of L. infantum amastigotes in the skin of asymptomatic seropositive dogs has been reported previously (Lainson & Rangel 2005, Madeira et al 2005, Dias et al 2011. In this study, parasitological examination showed the presence of amastigotes in bone marrow (100%), spleen and liver (54.5%), lymph nodes (45.4%) and skin (90.9%) in all asymptomatic dogs.…”
Section: Discussionmentioning
confidence: 70%
“…In Paracatu, Minas Gerais, 5% out of 267 dogs with positive serology for VL were asymptomatic (Dias et al 2011). The presence of L. infantum amastigotes in the skin of asymptomatic seropositive dogs has been reported previously (Lainson & Rangel 2005, Madeira et al 2005, Dias et al 2011. In this study, parasitological examination showed the presence of amastigotes in bone marrow (100%), spleen and liver (54.5%), lymph nodes (45.4%) and skin (90.9%) in all asymptomatic dogs.…”
Section: Discussionmentioning
confidence: 70%
“…Some authors have only isolated parasites from skin lesions (MADEIRA et al, 2005(MADEIRA et al, , 2006CASTRO et al, 2007). Moreover, Castro et al (2007) suggested that dogs are not good reservoirs for L. (V.) braziliensis and Massunari et al (2009) suggested that dogs have a secondary role in the transmission cycle of this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In wild and synantropic animals (considered potential reservoirs for L. braziliensis), such a distinction regarding tissue tropism does not exist (ROQUE et al, 2010;ROQUE & JANSEN, 2014), and the parasite may be detected in many organs. In dogs, this species has only been detected in cutaneous lesions (MADEIRA et al, 2005;DANTAS-TORRES, 2007). The visceralization detected herein by L. braziliensis may be a consequence of the impaired immune system of the dogs.…”
Section: Discussionmentioning
confidence: 69%
“…Cross-reactivity using Leishmania infantum antigen with sera from Leishmania braziliensis-infected dogs is commonly observed (BRASIL, 2006), but dog culling, in this case, is not recommended. Dogs infected with L. braziliensis commonly present localized skin lesions without systemic dissemination (MADEIRA et al, 2005). The urban reservoir of L. braziliensis is still not known in Brazil.…”
Section: Introductionmentioning
confidence: 99%